2015
DOI: 10.1051/0004-6361/201527202
|View full text |Cite
|
Sign up to set email alerts
|

Massive star formation by accretion

Abstract: Context. Massive stars likely form by accretion and the evolutionary track of an accreting forming star corresponds to what is called the birthline in the Hertzsprung-Russell (HR) diagram. The shape of this birthline is quite sensitive to the evolution of the entropy in the accreting star. Aims. We first study the reasons why some birthlines published in past years present different behaviours for a given accretion rate. We then revisit the question of the accretion rate, which allows us to understand the dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 36 publications
4
49
0
Order By: Relevance
“…Eggenberger et al 2008). In the present case, the central ingredient is accretion (Haemmerlé et al 2016), included through cold accretion; that is the entropy of the accreted gas matches that of the stellar surface (Palla & Stahler 1992). For rates of atomically cooled haloes, the effect of hot accretion (i.e.…”
Section: Methodsmentioning
confidence: 84%
“…Eggenberger et al 2008). In the present case, the central ingredient is accretion (Haemmerlé et al 2016), included through cold accretion; that is the entropy of the accreted gas matches that of the stellar surface (Palla & Stahler 1992). For rates of atomically cooled haloes, the effect of hot accretion (i.e.…”
Section: Methodsmentioning
confidence: 84%
“…For T Tauri stars, the measured disk mass loss rates are roughly a few percent of and linearly proportional to the mass accretion rates (Hartigan et al 1995;Rigliaco et al 2013;Natta et al 2014). However, younger class 0/I protostars tend to exhibit collimated Herbig-Haro jets (Reipurth & Bally 2001;Bally 2016), and are expected to have substantially lower accretion efficiencies (Behrend & Maeder 2001;Haemmerlé et al 2016Haemmerlé et al , 2019. To match the observed birthlines of intermediate-mass pre-MS stars on the HR diagram, Behrend & Maeder (2001) found that protostars accrete only ≈30% of the mass from the disk.…”
Section: Binary Accretionmentioning
confidence: 99%
“…To match the observed birthlines of intermediate-mass pre-MS stars on the HR diagram, Behrend & Maeder (2001) found that protostars accrete only ≈30% of the mass from the disk. Toward high accretion rates and more massive protostars, perhaps only ≈10% of the mass in the disk is accreted (Haemmerlé et al 2016).…”
Section: Binary Accretionmentioning
confidence: 99%
“…A general description of the code with rotation, without accretion, can be found in Eggenberger et al (2008). The treatment of accretion is detailed in Haemmerlé et al (2016Haemmerlé et al ( , 2017a. …”
Section: Stellar Evolution Codementioning
confidence: 99%